A new species of genus Homotechnes Candèze, 1882 from Guangxi, China (Coleoptera: Elateridae: Hypnoidinae) - Qiu, Lu; Ruan, Yong-Ying (Zootaxa, 2024)
Homotechnes choui sp. nov., a new species from Guangxi, China, is described and illustrated. An updated key and list of Chinese Homotechnes species, with corrected or supplementary distribution data, are provided.